Penerapan Integrated Marketing Communication PT. Telkom Indonesia Regional III dalam Meningkatkan Daya Saing dan Loyalitas Pelanggan - Jovita Rahma Adani; Lia Nirawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In response to the increasing competition within the telecommunications industry, PT. Telkom Indonesia Regional III faces the challenge of maintaining its competitive advantage and fostering customer loyalty. This study aims to analyze the application of Integrated Marketing Communication (IMC) by PT. Telkom Indonesia Regional III in enhancing the company’s competitiveness while simultaneously strengthening customer loyalty. The research employs a descriptive qualitative approach, utilizing data collection techniques such as interviews, observations, and document analysis. The findings reveal that PT. Telkom Indonesia Regional III has effectively implemented essential IMC elements, including advertising, sales promotions, digital marketing, personal selling, and public relations. These strategies have proven to be effective in increasing customer awareness of services, reinforcing long-term relationships, and supporting the company’s competitive positioning in the market.